Sustainable Development in The Academic Community as an Opportunity to Develop The Awareness of Urban and Rural Residents - Krzysztof Marecki; Agnieszka Wójcik-Czerniawska; Zbigniew Grzymała (Universitas Diponegoro, 2021)
The purpose of the article is to present the activities carried out by the Warsaw School of Economics, including the Department of Economics and Finance of the Local Government, aimed at both activities aimed at the diversified development of the broader sense - the activities of the Universities in this respect and in the strict sense, i.e. the activities of one of the departments, i.e. the Department of Economics and Finance of the Local Government within research and development at the local government level. The activities in the area of sustainable development include the membership to the Sustainable Development Goals Accord, the seat of the Polish branch of OIKOS International . On the other hand, activities in the field of sustainable development strictly mean activities in the field of research and development as well as conducting lectures and postgraduate studies in the field of sustainable development in the broad sense of the word. These activities are carried out by the mentioned department. The activities are therefore implemented on a large scale in order to increase the promotion of the idea of sustainable development in order to support the idea of sustainable development at every possible level, from national to local.